Effectiveness of Box Breathing on Respiratory Rate and Oxygen Saturation in Patients with COPD - Muhlisoh, Muhlisoh; Hasaini, Asni; Sukmawaty, Martini Nur (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chronic obstructive pulmonary disease (COPD) is a leading cause of death, with the majority of symptoms such as cough, dyspnea, and sputum production causing increased airway resistance. Breathing exercises are an important part of the pulmonary rehabilitation program, including box breathing. Objective: The purpose of this study was to analyze the effectiveness of box breathing on breathing frequency and oxygen saturation in patients with COPD at Idaman Banjarbaru Hospital. Method: research design Pretest-Posttest Control Group Design. The sample of this study was 20 respondents divided into 2 groups, namely the first group was the intervention group which was given Box Breathing treatment for 3 consecutive days with a duration of 15 minutes a day and the second group was the control group which only received therapy according to what was given by the hospital with purposive sampling. The research instrument was an observation sheet-bivariate data analysis using a Paired t-test and an Independent t-test. Results: There is a significant difference in the intervention group with the control group after being given box breathing on breathing frequency with an effectiveness value of 99.17%, but there is no significant difference in the intervention group with the control group after being given box breathing on oxygen saturation. It is recommended that the intervention of giving box breathing be used as one of the nursing interventions in patients with COPD as a management action for complaints of tightness.